Enriching Education with Exemplars in Practice: Iterative Development of Data Curation Internships - Matthew S. Mayernik; Cheryl A. Thompson; Valerie Williams; Suzie Allard; Carole L. Palmer; Carol Tenopir (International Journal of Digital Curation, 2015)
Partnerships between educational programs and research centers are vital to meeting the escalating workforce demands in data curation. They offer a platform for educators to increase their knowledge of current best practices and emerging challenges in the field. Student internships can be key to the success of these partnerships, not just for the students who gain authentic experience in facilities that excel at data intensive research and data services. Such partnerships provide an effective platform for rich and mutually beneficial engagement among educators, data professionals, scientists, and students. This paper reports on results from the Data Curation Education in Research Centers (DCERC) program aimed at developing a model for data curation education featuring field experiences in exemplar research centers. A strength of the DCERC model is its emphasis on facilitating mutual exchange of information among the DCERC program mentors and students. This model has evolved as a result of iterative and gradual refinements to the program model based upon information gathered from the formative evaluation. These refinements not only resulted in improved outcomes for the program participants but also, we believe, a more sustainable model for the program that leverages the knowledge base of the research scientists and students through peer-to-peer learning, rather than a traditional expert to trainee model. This paper describes formative evaluation findings that shaped the development of the DCERC program. We conclude with a discussion of the critical features of this model for the development of similar programs, and a data curation workforce that is able to accommodate and adapt to emergent data needs in a variety of environments.